2017
DOI: 10.1016/j.celrep.2017.06.086
|View full text |Cite
|
Sign up to set email alerts
|

AIM2 Engages Active but Unprocessed Caspase-1 to Induce Noncanonical Activation of the NLRP3 Inflammasome

Abstract: Inflammasomes are multimeric protein complexes that initiate inflammatory cascades. Their activation is a hallmark of many infectious or inflammatory diseases. Their composition and activity are specified by proinflammatory stimuli. For example, the NLRP3 inflammasome is activated in response to cell damage and K efflux, whereas the AIM2 inflammasome is activated in response to cytosolic DNA. We used Legionella pneumophila, an intracellular bacterial pathogen that activates multiple inflammasomes, to elucidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
9

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 58 publications
1
41
0
9
Order By: Relevance
“…We acknowledge that addition of LPS to study inflammasome activation in macrophages infected with Leishmania does not mimic natural infection. However, priming isolated cells prior infection is a common strategy to boost gene regulation and to synchronize inflammasome activation upon infection with many microbes including parasites, bacteria, and viruses . It is important to highlight that, in vivo, Leishmania parasites activate the inflammasome without the requirement of priming or LPS injection .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We acknowledge that addition of LPS to study inflammasome activation in macrophages infected with Leishmania does not mimic natural infection. However, priming isolated cells prior infection is a common strategy to boost gene regulation and to synchronize inflammasome activation upon infection with many microbes including parasites, bacteria, and viruses . It is important to highlight that, in vivo, Leishmania parasites activate the inflammasome without the requirement of priming or LPS injection .…”
Section: Discussionmentioning
confidence: 99%
“…However, priming isolated cells prior infection is a common strategy to boost gene regulation and to synchronize inflammasome activation upon infection with many microbes including parasites, bacteria, and viruses. 26,[45][46][47][48] It is important to highlight that, in vivo, Leishmania parasites activate the inflammasome without the requirement of priming or LPS injection. 25,27,29,49 We believe that this occur because of tissue damage caused during infection, the release of alarmins, such as ATP, IL-1 , and high mobility group box 1 (HMGB1), and also other inflammatory mediators such as IFN-and TNF-, which can boost NF-B signaling and are extremely important in the pathogenesis of Leishmania infections.…”
Section: Discussionmentioning
confidence: 99%
“…Various recent studies reported clues about the caspase-11 non-canonical inflammasome-mediated activation of the NLRP3 canonical inflammasome. Potassium ion (K + ) efflux is a critical determinant for the activation of NLRP3 canonical inflammasome, and caspase-11 non-canonical inflammasome activated NLRP3 canonical inflammasome by facilitating K + efflux through cell membrane damage and the pores generated by N-GSDMD, bacterial pore-forming toxins, and P2X 7 [37,[39][40][41].…”
Section: Caspase-11 Non-canonical Inflammasome-activated Inflammatorymentioning
confidence: 99%
“…pneumophila indirectly activates NLRP3 through the caspase-11 and absent in melanoma 2 (AIM2) inflammasomes. 57,58 Bacterially-induced metabolic changes may also indirectly affect NLRP3 activation and innate immune function more broadly.…”
Section: Bacterial Infectionmentioning
confidence: 99%